The Implementation of Problem Based Learning with Mind Mapping to Improve The Student’s Understanding of Concept (Journal of Primary Education, 2018)
The purpose of this research was, (1) to describe the implementation of PBL model with mind mapping to improve students' understanding of concept, and (2) to analyze the improvement of understanding of concept of the students after the implementation of PBL model with mind mapping. This type of research is mixed methods with sequential explanatory strategy. Samples of this research was the fourth grade students of SDN 5 Puyoh with 30 students. The first method applied in this research was quantitative method with one group pretest-posttest design, followed by the method of data collection techniques by using test in the form of multiple choice questions, as well as non-test which consists of interview, observation, and documentation. The results showed that (1) the implementation of PBL model with mind mapping had succeeded in increasing the understanding of concept of students with the achievement of three indicators: the average posttest student conceptual understanding reached the minimum mastery criteria, the increase of students' understanding of concept is in the category of at least moderate according to N-Gain test, the average score achieved by the N- gain test was 0.36 which is in the medium category, and the average score of the acquisition of the create of mind mapping is also in the minimum good category, the average score obtained is 22, (2) the learning conducted by using PBL and mind mapping can improve students' understanding of concept, the Sig value obtained is 0.00 < 0.05, therefore, it can be concluded that there is an increased of understanding of concept of students after the implementation of PBL model with mind mapping.